Analisis Semiotika Model Roland Barthes Pada Makna Pujian Kelompok Purwa Ayu Mardi Utama (PAMU) - Fatmarahadi, Shella Syakhfiani (Journal of Communication Studies, 2024)
This research aims to analyze the meaning of the praises of the Purwa Ayu Mardhi Utama (PAMU) group using Roland Barthes' semiotic theory, which includes three levels of meaning: denotation, connotation and myth. PAMU is an Islamic-based mysticism group from Surakarta. They sing praises which mean prayers with cultural, spiritual and moral values. Denotatively, the praise lyrics describe the concept of human life regarding time, life and death, with an emphasis on the importance of responsibility and utilization of time. Connotatively, these lyrics evoke emotions about wisdom, steadfastness, and a spiritual relationship with God. On a mythical level, the lyrics reflect the cycle of life and the teaching that good deeds will continue to be remembered and passed down. This research used qualitative research using the Content Analysis method or content analysis. This technique allows writers to understand how certain symbols reflect values, culture, or messages in a particular context. The main instrument in this research is the researcher himself, who directly observes, listens and listens to praise from the PAMU group. The research results show that PAMU praise is not only a form of artistic expression, but also a medium for teaching religious and cultural values. This research recommends preserving PAMU's praise as cultural heritage as well as further studies to explore its relevance to modern life